Occupational Stress Experienced by Nurses Working in a Greek Regional Hospital: A Cross-sectional Study - Chatzigianni, Dimitra; Tsounis, Andreas; Markopoulos, Nikolaos; Sarafis, Pavlos (My University, 2018)
Occupational stress is both psychologically and physically challenging and may lead to high rates of absenteeism, burnout, and turnover. Nursing is considered as one of the most stressful and demanding professions. This study aims to measure perceived stress levels among nurses in a Greek public general hospital.
Keywords: Greece; Hospitals; Nursing; Occupational health